2019
DOI: 10.1080/15548627.2019.1596483
|View full text |Cite
|
Sign up to set email alerts
|

HIF1A and NFAT5 coordinate Na+-boosted antibacterial defense via enhanced autophagy and autolysosomal targeting

Abstract: Infection and inflammation are able to induce diet-independent Na +-accumulation without commensurate water retention in afflicted tissues, which favors the pro-inflammatory activation of mouse macrophages and augments their antibacterial and antiparasitic activity. While Na +-boosted host defense against the protozoan parasite Leishmania major is mediated by increased expression of the leishmanicidal NOS2 (nitric oxide synthase 2, inducible), the molecular mechanisms underpinning this enhanced antibacterial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 94 publications
(130 reference statements)
8
76
0
Order By: Relevance
“…To further assess the role of increased osmolality and Na + content on osteoclastogenesis, we exposed RANKL/M-CSFtreated WT RAW264.7 cells to either an increase of 40 mM NaCl (HS¢) or 80 mM mannitol. In contrast to NaCl, mannitol represents a nonionic osmolyte that is known to increase tonicity but does not penetrate the cell membrane (41,42). Exposure to HS¢ or mannitol increased Nfat5 levels in RANKL/ M-CSF-treated WT RAW264.7 cells ( Figure 2A) and BM-derived macrophages (Supplemental Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further assess the role of increased osmolality and Na + content on osteoclastogenesis, we exposed RANKL/M-CSFtreated WT RAW264.7 cells to either an increase of 40 mM NaCl (HS¢) or 80 mM mannitol. In contrast to NaCl, mannitol represents a nonionic osmolyte that is known to increase tonicity but does not penetrate the cell membrane (41,42). Exposure to HS¢ or mannitol increased Nfat5 levels in RANKL/ M-CSF-treated WT RAW264.7 cells ( Figure 2A) and BM-derived macrophages (Supplemental Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, exposure of macrophages to HS¢ impaired the regulatory, antiinflammatory activity of macrophages (41), while increases in local Na + enhanced their antimicrobial activity. Increases in Na + have been demonstrated to help fight against the protozoan parasite Leishmania major (45) and against the bacterial pathogen E. coli (42,50). Recent evidence also suggests that elevation in Na + facilitates antiviral responses against vesicle stomatitis virus (51).…”
Section: Discussionmentioning
confidence: 99%
“…However, the other upstream regulators need to be further explored in future laboratory experiments. The STAT1, STAT4, IRF1 and HIF1A that were predicted in the current study as the upstream regulators associated with NO-Based index at both 3 and 18 hours after treatment (Supplementary Table 11 and 12), are all known key transcription regulators that shape the proinflammatory response of macrophages [37][38][39] . In a mouse model, IRF8, IRF1, STAT1 and PU.1 have been shown to be a key regulator of macrophage proinflammatory and antimicrobial response by using the combination of ChIP-Seq and RNA-seq techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that NFAT5 and HIF-1α worked in coordination in macrophages and nucleus pulposus cells (Gogate et al, 2012;Neubert et al, 2019). The above results suggested that they both regulate OGD-induced aberrant NKCC1 expression in hippocampal neurons.…”
Section: Relationship Between Nfat5 and Hif-1α In Hippocampal Neuronsmentioning
confidence: 68%
“…Previous research demonstrated that HIF-1α and NFAT5 regulated diet-independent Na + accumulation-induced proinflammatory activation of mouse macrophages, and NFAT5 was important for Na + accumulation-induced HIF-1α upregulation (Neubert et al, 2019). NFAT5 stimulated HSP90 expression while HIF-1α inhibited HSP90 expression in hypoxic nucleus pulposus cells (Woo et al, 2002;Gogate et al, 2012).…”
Section: Discussionmentioning
confidence: 96%